Perceived contributory leisure in the context of hobby beekeeping: A multi-country comparison - Duarte Alonso, Abel; Kok, Seng Kiat; O'Shea, Michelle (Taylor & Francis, 2020)
This comparative study investigates the motivation and perceived contributions underpinning hobby beekeepers, as well as how they perceive appreciation and/or awareness of their contribution among the broader society. An online questionnaire gathered data from 800 hobby beekeepers in Australia, New Zealand, and the United Kingdom. Beekeeping is predominantly practiced as a hobby (62.3%), which is distantly followed by helping to protect the environment and an interest in beekeeping in terms of motivations for participation. In addition, pollination, supporting the food chain, and preserving nature were revealed as key contributions of hobby beekeeping. Over half of participants perceived limited concern, awareness, and appreciation among external stakeholders (e.g., the public, society). Various intergroup differences concerning the main dimensions explored were confirmed. The overall findings allowed the development of a model which highlights the significance of ‘perceived contributory leisure’, whereby participants’ leisure activities can have wider societal implications.